NON-PHARMACOLOGICAL APPROACHES IN FIBROMYALGIA: EXERCISE, MANUAL THERAPY AND INNOVATIVE TECHNOLOGY-BASED INTERVENTIONS - Alicja Hojda; Filip Bednarek; Olga Plinta; Natalia Nawrocka; Hanna Rodak; Izabela Małajewicz; Małgorzata Pietrzyk; Dawid Stępień; Karolina Oskroba (International Journal of Innovative Technologies in Social Science, 2026)
Background. Fibromyalgia is a chronic disorder characterized by widespread pain, fatigue, sleep disturbances, and mood disorders, affecting predominantly middle-aged women. Its complex pathophysiology involves both central and peripheral mechanisms, with management aimed at relieving symptoms while improving quality of life. Non-pharmacological interventions, including exercise, manual therapy, mind-body practices and emerging approaches like dry needling and virtual reality, show promise in improving patient outcomes. Aim. To review current evidence on non-pharmacological interventions for fibromyalgia, focusing on their efficacy, safety and impact on pain, physical function, symptom management and quality of life. Material and methods. A narrative review of studies from 2010–2025 was conducted using PubMed, ScienceDirect, and Google Scholar. Relevant articles were identified with keywords related to fibromyalgia and non-pharmacological treatments and the data was categorized by intervention type. Results. Non-pharmacological interventions for fibromyalgia, including low-impact exercise, manual therapy, dry needling, acupuncture, cryotherapy and virtual reality, improve pain, physical function, fatigue, mood and quality of life. Exercise and mind-body practices enhance both physical and psychological well-being, while manual therapy and dry needling techniques reduce pain and improve sleep. Cryotherapy decreases inflammation and virtual reality shows promising effects on symptoms and enables home-based rehabilitation. Conclusions. Non-pharmacological interventions, provide significant benefits for fibromyalgia, improving pain, fatigue, sleep and quality of life. Aquatic exercises offer short-term relief, while resistance and mind–body training support long-term improvements. Individualized, multidisciplinary approaches remain essential, and further research is needed to optimize treatment protocols.